Analysis of Rabbit Farming Business and Marketing in Increasing Family Income from a Sharia Economic Perspective - Tang, Muhammad; Hasriadi, Hasriadi (ETDC: Indonesian Journal of Research and Educational Review, 2023)
The Sharia economic law approach is intended to explore aspects of the problem of business analysis and marketing of rabbit livestock from the perspective of Sharia economic law. The psychological approach is to gain knowledge related to the psychological condition of the informant relating to behavior, knowledge, feelings, and thoughts about the object being studied. The sociological approach takes a social approach to rabbit breeders and buyers. Mattoanging Village, Lalabata District, Soppeng Regency, is the center of rabbit farming in Soppeng Regency. In Mattoanging Village, there are several heads of families who are involved in rabbit farming activities. Currently, the number of breeders who are starting to pursue business is increasing, and marketing is also getting better. This shows that the growing interest of breeders is supported by market opportunities that are still very open. The rabbit farming business is currently being developed by breeders as an effort to increase productivity from a good perspective for health and income. Apart from that, the Break Even Point (BEP) analysis, namely the level of revenue, production, and price of the rabbit breeder's business, is at the break-even point or does not make a profit and does not experience a loss.